Secondary Control for Cyber-Physical Interconnected Microgrid Systems - Luu, Ngoc An; Nguyen, Tung Lam (Engineering, Technology & Applied Science Research, 2025)
This paper presents a comprehensive analysis of the design, control frameworks, and practical implementation of interconnected microgrids, with an emphasis on improving system resilience and reliability. To overcome architectural challenges, a hierarchically distributed control system is proposed, featuring both microgrid-level and system-wide control layers. A multi-agent system is employed to oversee control elements in each microgrid and to facilitate cooperation with neighboring grids. Additionally, the paper introduces a Cyber Hardware-in-the-Loop (CHIL) framework, designed to function as a real-time simulation platform for the cyber-physical aspects of these systems, integrating network emulation, real-time power system dynamics, and multiagent control coordination.